Pengaruh Kepemimpinan Kepala dan Peranan Komite Madrasah Terhadap Kinerja Guru Madrasah Aliyah di Kabupaten Banjarnegara - natir natir (Balai Diklat Keagamaan Semarang, 2021)
The leadership of the madrasa head and the role of the madrasa committee are two factors that influence teacher performance. The type of this research is a field research with data collection techniques using a questionnaire by means of proportionate stratified random sampling. While the data analysis use descriptive methods and multiple regression analysis. The results show that there are; 1) an influence of headmaster leadership on teacher performance by calculating T value of 5.983 with a significance of 0.000 (p <0.05). 2) an influence of Madrasah committee’s role on teacher performance of T value of 3.704 with a significance of 0.000 (p <0.05), 3. an influence of headmaster leadership and Madrasah committee’s role on Madrasah Aliyah teacher performance in Banjarnegara Regency of F value of 87.501 with a significance of 0.000 (p <0.05). The leadership of headmaster is the dominant factor influencing the performance of Madrasah Aliyah teachers in Banjarnegara Regency.